ASSESSING ABILITY ON SPEAKING ENGLISH OF STUDENTS OF SMPN NEONBAT - luruk, maria; Kamlasi, Imanuel; Bouk, Edmundus (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2021)
The current research was carried out in order to answer the following questions: 1) What are the level of the students’ ability in speaking English and 2) What are the difficult aspects in speaking English. This research was conducted on the students of grade VIIIA of SMP Negeri Neonbat, in North Central Timor Regency. The subject of the research was the eighth grade students consisted of 20 students. A speaking test, observation and documentation were the instruments for collecting the data. The researcher took three topics in speaking test mentioned as: 1) telling short story, 2) telling daily activity and 3) describing people. In analyzing the data, the researcher implemented qualitative method. The data then be analysed following eight steps as follows: 1)playing the record, 2) replaying the record, 3) transcribing, 4) codifying, 5) categorizing, 6) tabulating, 7) analysing and 8) discussing. Based on the result of the data analysis, it was found out that the students’ level of ability in speaking was good and the average score is 79.62. Vocabulary and grammar aspects are still difficult for the students in speaking English since the scores for those two aspects were lower than the aspects of pronunciation and idea. Keywords: assessing, speaking, ability.